2019
DOI: 10.1055/s-0039-3400982
|View full text |Cite
|
Sign up to set email alerts
|

Is Nasal Septum–Tragus Length Measurement Appropriate for Endotracheal Tube Intubation Depth in Neonates? A Randomized Controlled Study

Abstract: Objective Endotracheal intubation is a frequent procedure performed in neonates with respiratory distress. Clinicians use different methods to estimate the intubation insertion depth, but, unfortunately, the improper insertion results are very high. In this study, we aimed to compare the two different methods (Tochen's formula = weight in kilograms + 6 cm; and nasal septum–tragus length [NTL] + 1 cm) used to determine the endotracheal tube (ETT) insertion depth. Study Design Infants who had intubatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 16 publications
2
17
0
Order By: Relevance
“…We found that NTL significantly overestimated the OTD in term infants, which is consistent with the findings of Wang et al (22). However, a recent Turkish study reported different results, and found that NTL + 1 cm was more likely to overestimate OTDs in infants <1,500 g and those with a GA < 34 weeks (19). NTL also overestimated OTDs in the SGA infants in the current study.…”
Section: Shading Explanationsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that NTL significantly overestimated the OTD in term infants, which is consistent with the findings of Wang et al (22). However, a recent Turkish study reported different results, and found that NTL + 1 cm was more likely to overestimate OTDs in infants <1,500 g and those with a GA < 34 weeks (19). NTL also overestimated OTDs in the SGA infants in the current study.…”
Section: Shading Explanationsupporting
confidence: 92%
“…This also means that age had a greater influence on NTL than BW, which has never been reported in previous studies. The efficacy of NTL + 1 cm in other studies has been reported to be as low as 32.7%, and most of these studies have attempted to refine the efficacy of NTL estimates using BW adjustments (19,20,22). Following adjustments for age, there was a 110% improvement in the overall efficacy of NTL estimations and a reduction of over 20% in the rates of too-deep intubations.…”
Section: Shading Explanationmentioning
confidence: 99%
“…Our unpublished data showed using the NTL method for estimating ETT insertion depth in term and preterm infants result in 35% of correctly positioned ETT tips. The data is similar to the randomised20 and non-randomised21 studies that showed similar accuracy (32%–37%) with the NTL method for estimating ETT insertion depth. With 90% power and two-sided 5% significance, to detect an absolute increase of 15% in optimally positioned ETT tips using the gestational age method, we will require 454 participants.…”
Section: Methodssupporting
confidence: 82%
“…However, a randomised trial found no difference between gestational age and weight-based methods for estimating ETT insertion depth in newborns 15. Similarly, observational studies report the NTL method—the distance from nasal septum tip to ear tragus+1 cm—for estimating ETT insertion depth improves the proportion of optimally placed ETT tips in neonates,16–19 but no difference between the NTL method and weight-based method was found in a recent randomised trial 20…”
Section: Introductionmentioning
confidence: 96%
“…The size and depth of the ETT are calculated using several methods (Table I). (83)(84)(85)(86)(87) The position of the ETT is confirmed by observing chest rise, auscultation for equal breath sounds and prompt increase in HR. Capnography or colorimetric detection of carbon dioxide may be used to ensure appropriate tracheal placement of the ETT, especially during the transport of an intubated newborn.…”
Section: Endotracheal Intubation and Laryngeal Mask Airway Endotracheal Intubationmentioning
confidence: 85%